Banned Books Week Read-Out - Sonoma State University Library (Sonoma State University)
Banned Books Week is an annual event acknowledging the freedom to read and the importance of the First Amendment. Join the University Library and students and faculty of Sonoma State for a read-out of banned books on the ramp of the Schulz Information Center at noon on September 28, September 29, and September 30. The read-outs will feature different readers reading from a banned book and discussing some of the reasons the title was banned or challenged. On Wednesday 9/28, students from the English Department's Young Adult Literature class will read from banned teen books. Thursday 9/29 will feature Dean Thaine Stearns, Arts and Humanities, and English professors Kim Hester-Williams and Brantley Bryant. On Friday, 9/30 readers will include professors Ben Ford, Math and faculty Chair, Margie Purser, Anthropology and Chair-Elect, and Laura Watt, Environmental Studies and Planning. Held during the last week of September, Banned Books Week highlights the benefits of free and open access to information while drawing attention to the harms of censorship by spotlighting actual or attempted bannings of books across the United States and the world. This is an opportunity each year to teach the importance of our First Amendment rights and the power of literature, and to draw attention to the danger that exists when restraints are imposed on the availability of information in a free society.